2022
DOI: 10.3389/fcell.2022.845461
|View full text |Cite
|
Sign up to set email alerts
|

Early Deletion of Neurod1 Alters Neuronal Lineage Potential and Diminishes Neurogenesis in the Inner Ear

Abstract: Neuronal development in the inner ear is initiated by expression of the proneural basic Helix-Loop-Helix (bHLH) transcription factor Neurogenin1 that specifies neuronal precursors in the otocyst. The initial specification of the neuroblasts within the otic epithelium is followed by the expression of an additional bHLH factor, Neurod1. Although NEUROD1 is essential for inner ear neuronal development, the different aspects of the temporal and spatial requirements of NEUROD1 for the inner ear and, mainly, for aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Notably, the functional and spatial organization of SGNs may differ in transcription factor networks required for their differentiation programs. For example, some Neurod1 -lacking neurons survive, form a rudimental cochlear ganglion, and establish bipolar connections to their targets in Neurod1 -null mice ( 12 ) or the otocyst-deleted Neurod1 conditional mutant ( 18 ). Consistent with these findings, neurons forming a segment of the spiral ganglion in the Rosenthal’s canal of Isl1CKO may not require ISL1 for their differentiation and the migration mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the functional and spatial organization of SGNs may differ in transcription factor networks required for their differentiation programs. For example, some Neurod1 -lacking neurons survive, form a rudimental cochlear ganglion, and establish bipolar connections to their targets in Neurod1 -null mice ( 12 ) or the otocyst-deleted Neurod1 conditional mutant ( 18 ). Consistent with these findings, neurons forming a segment of the spiral ganglion in the Rosenthal’s canal of Isl1CKO may not require ISL1 for their differentiation and the migration mode.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors govern the development of inner ear neurons, including NEUROG1 ( 11 ), NEUROD1 ( 12 ), GATA3 ( 13 , 14 ), and POU4F1 ( 15 ). The transcription factor NEUROD1 is vital for the differentiation and survival of inner ear neurons ( 16 18 ). We previously demonstrated that Isl1 Cre -mediated Neurod1 deletion ( Neurod1CKO ) results in a disorganized cochleotopic projection from SGNs ( 19 ), affecting acoustic information processing in the central auditory system of adult mice at the physiological and behavioral levels ( 20 ).…”
mentioning
confidence: 99%
“…Notably, the functional and spatial organization of SGNs may differ in transcription factor networks required for their differentiation programs. For example, some Neurod1 lacking neurons survive, form a rudimental cochlear ganglion, and establish bipolar connections to their targets in Neurod1 null mice 11 or the otocyst-deleted Neurod1 conditional mutant 17 . Consistent with these findings, neurons forming a segment of the spiral ganglion in the Rosenthal’s canal of Isl1CKO may not require ISL1 for their differentiation and/or the migration mode.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors govern the development of inner ear neurons, including NEUROG1 10 , NEUROD1 11 , GATA3 12, 13 , and POU4F1 14 . The transcription factor NEUROD1 is vital for the differentiation and survival of inner ear neurons 15, 16, 17 . We previously demonstrated that Isl1 Cre -mediated Neurod1 deletion ( Neurod1CKO ) results in a disorganized cochleotopic projection from SGNs 18 , affecting acoustic information processing in the central auditory system of adult mice at the physiological and behavioral levels 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Development of the inner ear is an organized molecular transformation of a set of epidermal cells (the otic placode) into the fully developed ear with its neurosensory component, necessary for signal extraction and transmission, and the non-sensory component, forming the labyrinth necessary for directing sensory stimuli to specific sensory epithelia [6,94]. The main genes involved in neurosensory development in the inner ear are MYO7A, HES5, SOX2, NEUROG1, NEUROD1, and POU4F1 [80,[95][96][97][98].…”
Section: Clinical Applications In Genetic Deafness and Vestibular Dis...mentioning
confidence: 99%